P099 Physiological phenotypes of obstructive sleep apnoea (OSA) in Pacific Islanders and equally obese Caucasians. (7th October 2021) - Naidoo, C; Landry, S; Edwards, B; O'Driscoll, D; Johnson, P; Wheatley, J; Lambert, S; Kairaitis, K
Abstract: Background: Pacific islanders (PI) have a high prevalence of severe OSA, attributed to obesity. Ethnic differences in mechanisms contributing to OSA have been reported. We compared physiological polysomnography characteristics in obese PI and Caucasian (C) patients with OSA. Methods: Retrospective polysomnography (PSG) studies from a tertiary hospital sleep laboratory were identified for PI and age, gender and BMI matched C patients (BMI>30 kgm²). All PSGs were rescored by a single scorer, and pharyngeal collapsibility (Vpassive), upper airway muscle compensation (Vcomp), arousal threshold (AT), [all expressed as percentage of steady-state breathing (Veupnea)], and loop gain (LG) were determined non-invasively via established/validated techniques. Progress to date 14 PI [8 female] and 29 C [15 female] were identified. There were no differences in age [52.2±17.0 PI; 52.5±13.3 C years], BMI [46.9±7.7 PI; 48.2±10.1 C kgm²] or AHI (35.6 [17.9–77.5] PI; 41.2 [20.9–83.6] C events/hour) (mean±SD or median[IQR]; all p>0.4; paired t-test or Wilcoxon signed rank). There were no significant differences in Vpassive (88.8 [88.4–97.1] PI; 91.8 [44.4–95.8]C %Veupnea; p=0.38), Vcomp (1.2 [-12.0–9.2] PI; 5.8 [-1.9–9.6] C %Veupnea; p=0.30), AT (131.4 [110.5–140.8] PI; 126.1 [110.4–180.7] C %Veupnea; p=0.67) or LG (0.6±0.1 PI; 0.7±0.3 C; p=0.23). Intended outcome and impact In a small cohort of PI and age, gender and BMI matched C with OSA, upper airway obstructive event frequency was the same and there were no differences in physiological phenotypes, suggesting similar mechanisms contribute to OSA severity in both groups. Confirmation of these findings in a larger cohort is ongoing.